The study on The Philosophy of Zhao Lun - Li Yan (SHS Web of Conferences, 2024)
Zhaolun is the master work written by Sengzhao. I will choose one of most precious commentaries, Zhao Lun Ji Jie Ling Mo Chao, which I study, and translate into English, as nobody has done this work till now. In the studies of Zhaolun, some unsolved questions and divergences still exist. Based on the works of scholars in China and abroad, I try to explain some questions more properly on grounds. Zhaolun deeply affected the Buddhism in China, as well in Korea and Japan. I study Zhaolun based on the general explanation to the notes and commentaries in different Dynasties.